Theory‐driven development of a comprehensive turnover‐attachment motive survey - Maertz, Carl P.; Boyar, Scott L. (Human Resource Management, 2012)
AbstractRecent studies propose a theoretical framework of “eight forces” that purportedly captures all the distinct motives causing voluntary turnover decisions. Based on this framework, we develop the Turnover‐Attachment Motive Survey (TAMS) consisting of 18 scales, the most comprehensive model‐based turnover antecedent survey to date, facilitating more fully specified research models and more systematic diagnoses of turnover causes. Moreover, findings support behavioral inertia against quitting, psychological dissonance costs of quitting, supervisor continuance attachment, and coworker continuance attachment as significant predictors of turnover behavior for the first time in the literature. Overall, findings do suggest that our 18‐scale survey demonstrated adequate psychometric properties to justify its further use and development. We finally discuss the many uses of the TAMS for both turnover researchers and practitioners. © 2012 Wiley Periodicals, Inc.